Hepatopulmonary shunting in patients with primary and secondary liver tumors scheduled for radioembolization. Issue 2 (February 2015) - Powerski, Maciej Janusz; Erxleben, Christoph; Scheurig-Münkler, Christian; Geisel, Dominik; Heimann, Uwe; Hamm, Bernd; Gebauer, Bernhard
Highlights: We try to find predictive factors for hepatopulmonary shunting. Hypervascularized tumors have higher shunts than low vascularized tumors. HCC and colorectal cancer are associated with higher shunts than breast cancer. Portal vein occlusion is associated with increased hepatopulmonary shunting. There is poor correlation of hepatopulmonary shunting and tumor or liver volume. Abstract: Purpose: In patients undergoing transarterial radioembolization (RE) of malignant liver tumors, hepatopulmonary shunts (HPS) can lead to nontarget irradiation of the lungs. This study aims at analyzing the HPS fraction in relation to liver volume, tumor volume, tumor-to-liver volume ratio, tumor vascularity, type of tumor, and portal vein occlusion. Materials and methods: In the presented retrospective study the percentage HPS fraction was calculated from SPECT/CT after infusion of Tc-99m macroaggregated albumin (Tc-99m MAA) into the proper hepatic artery of 233 patients evaluated for RE. Results: HPS fractions correlate very weakly with liver volume ( r  = 0.303), tumor volume ( r  = 0.345), and tumor-to-liver volume ratio ( r  = 0.340). Tumors with strong contrast enhancement (HPSmedian(range)  = 11.7%(46.3%); n  = 73) have significantly larger shunt fractions than tumors with little enhancement (HPS = 8.3%(16.4%); n  = 61; p  < 0.001). Colorectal cancer metastases (HPS = 10.6%(28.6%); n  = 68) and hepatocellular cancers (HPS = 11.7%(39.4%); n  = 63) have significantly larger HPS fractions than metastases from breast cancer (HPS = 7.4%(16.7%); n  = 40; p  = 0.012 and p  = 0.001). Patients with compression (HPS = 13.9%(43.7%); n  = 33) or tumor thrombosis (HPS = 15.8% (31.2%); n  = 33) of a major portal vein branch have significantly higher degrees of shunting than patients with normal portal vein perfusion (HPS = 8.1% (47.0%); n  = 167; both p  < 0.001). The shunt fraction is largest in patients with HCC and thrombosis or occlusion of a major portal vein branch (HPS = 16.6% (31.0%); n  = 32). Conclusion: The degree of hepatopulmonary shunting depends on the type of liver tumor, tumor vascularity, and portal vein perfusion. There is little to no correlation of HPS with liver volume, tumor volume, or tumor-to-liver volume ratio.